IMPLEMENTASI METODE PEMBELAJARAN INDUKTIF DAN INTERNALISASI SCIENTIFIC ATTITUDE DALAM UPAYA PEMBENTUKAN KARAKTER MAHASISWA PADA MATA KULIAH PRAKTIKUM ANATOMI FISIOLOGI MANUSIA - Endang Srilestari (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2016)
Human Anatomy Physiology subject has not been able to increase the student scientific attitude. Students mostly poor on the technical aspects and the current theories in laboratories work, and neglect scientific attitude. Therefore we need a new breakthrough in the learning process, in efforts to establish the students character. The aims of this research was to determine how the implementation of inductive learning methods and internalization of students attitude in efforts to establish the students character. This was a Classroom Action Research that consist of two cycles. In each cycle there are four phases: 1) planning, 2) action, 3) observation, and 4) reflection. The research result showed that inductive learning methods and internalization scientific attitude was able to increase the student character.